Design Aplikasi “Hadis-Hadis Sains” Melalui Website Kodular - Nadya Silvy (Ikhlas : Jurnal Ilmiah Pendidikan Islam, 2025)
Science and technology became something that developed very rapidly in the classical period and Islamic civilization. And this proves that epistemology developed at that time. Even though in the past Muslim scholars studied a lot in the field of Islamic civilization, with their epistemology they were able to provide the best in the field of science and technology and develop it to all corners of the world. Technology is a source of information today. It is necessary to know that the hadiths of the Prophet Muhammad contain many Hadiths about Science and Technology. What is contained in the hadith is mentioned implicitly in the rules of explanation of creed and faith. That is why, hadith will always coexist with the development of the times and there will be no conflict between the two forever. The "Hadith-Hadith Science" application is research that uses the R&D (Research and Development) method and in its development uses the ADDIE (Analysis, Design, Development and Evaluation) method.  Then this application was developed via the Kodular.Io website which can be accessed on Chrome, Mozilla Firefox and Google. This application contains 40 selected hadith themes about Science in hadith. By developing the "Scientific Hadiths" application, researchers hope that this application can be useful for users.